Genome Sequencing and Bioinformatic Analysis of Pasteurella multocida Serotype B:2 Strain PMTB - Wan Mohamad Nazarie, Wan Fahmi (2011)
Pasteurella multocida is a Gram-negative bacterium, which is the causative agent of a wide range of diseases in animals. This organism usually resides in the mucous membrane of the intestinal, genital and respiratory tissues and is an opportunistic pathogen that causes fowl cholera, bovine haemorrhagic septicaemia and porcine atrophic rhinitis. So far, only complete genome of P. multocida serotype A:3 strain Pm70 has been elucidated. This study was conducted to sequence the genome of P. multocida serotype B:2 strain PMTB and to compare with the complete genome of Pm70. A total of 7.2 million sequence reads were generated from Illumina Genome Analyzer. De novo sequence assembly followed by comparison with Pm70 reference sequence produced a partial near-complete genome of PMTB with missing nucleotide sequences located in 81 gaps. The partial genome of P. multocida strain PMTB is 97.78% identical to Pm70. The estimated size of the partial genome of PMTB is 2,208,894 bp while the Pm70 genome is 2,257,487 bp. In addition, both genomes contain similar % GC content 40 to 41%. Analysis using GeneMark software indicated the total genes of the partial genome of PMTB are 2078 while the reference genome Pm70 has 2014 genes. Gene comparison between PMTB and Pm70 to construct PMTB sequences as a database blast against Pm70 sequences showed there are 223 unique genes found in PMTB but absence in Pm70. The unique genes are probably specific to serotype B:2 only or the genes were not detected in sequence analysis since they are located in the missing sequences in the gaps. On the other hand, a total of 49 genes are not detected in partial PMTB genome but present in Pm70. Sequence analysis also showed the presence of genes with high similarity (99 to 100%) to the genes from previously characterized serotype B:2, genes that are also found in other P. multocida serotypes and genes found in other bacteria especially Haemophilus influenza, Actinobacillus minor and Vibrio cholerae. Based on the partial genome sequence analysis, there are probably several virulence genes and virulence-associated genes in the P. multocida PMTB genome which include adhesins protein [type 4 fimbria (ptfA)], serotype–specific capsular polysaccharide, lipopolysaccharide, iron acquisition related genes such as Exbd and tonB, gene associated hemoglobin binding protein (HgbA), gene encode for transferrin-binding protein (tbpA), and several uncharacterized secreted enzymes and proteins that play important role in the pathogenicity of the disease. Complete genome sequencing and genome-wide functional genomics studies on P. multocida PMTB genome will be able to provide valuable information on pathogenicity of haemorrhagic septicaemia in ruminants.